Psychological Factors Associated with Adolescent Motherhood in Mothers Under 15 Years Old - Valdivia P, Maruzzella (Revista de Psicología, 2003)
The present research analyzes psychological variables associated with Adolescent motherhood; comparing young mothers under 15 years old, with mothers between 20 and 34 years old, and adolescents non mothers neither pregnant in a comparative descriptive transversal study. The adult mothers didn’t show significant higher levels of perceived social support than adolescent mothers under 15 years old (p=0.46), neither a significant higher intelectual level than adolescent mothers under 15 years old (p=0.23). Besides, it didn’t show a higher total self-steem level than adolescent mothers under 15 years old (p=0.5). Nevertheless, the adolescent mothers had a significant higher level of social self-steem than the adult mothers (p=0.036). The adolescents non mothers, didn’t show a higher level of perceived social support, than the adolescents mothers (p=0.45) and in the sub-scale, perceived social support from others; the adolescent mothers had higher levels of perceived social support than the non pregnant adolescents (p=0.002). On the other hand, the adolescents no mothers showed a significant higher intelectual level than the adolescens mothers (p=0.017). The adolescent mothers didn’t show a higher level of depressive symptomatology than the adolescents non mothers. On the contrary, the adolescent non mothers showed significant higher levels of depressive symptomatology (p=0.032). The adolescent non mothers didn’t had a significant higher level of self-steem than the adolescent mothers (p= 0.12). However, a weak significant differences was found in school self-steem (p=0.07) and in general self-steem (p= 0.09), the adolescents mothers having higher average than the adolescent non mothers. The findings invite us to think about cognitive development, particulary on the IQ and the personal narrative. The interaction of both factors leave the adolescents and their sons and daughters in a risky situation and vulnerability, important to consider it in future research and interventions